L J,so it looks like you are dealing with systems of equations.

I'll solve it for you real quick below.

-2x- 2y = 6

y = 3x - 5

The best method to use is to solve with substitution.

Step 1:

Write the equations.

y = 3x - 5

-2x- 2y = 6

Step 2: Solve for Y in y = 3x - 5

Notice that Y is already given, which is 3x - 5,

so:

Step3:Substitute 3x - 5 for y in -2x- 2y = 6

-2x - 2y = 6

-2x - 2(3x - 5) = 6

-8x + 10 = 6

Step 4: Isolate -8x

-8x+ 10 - 10 = 6 - 10

-8x= -4

Step 5: Isolate x further by dividing by -8 on both sides

-8x / -8 = -4 / -8

x = 1/2. So no, X is not equal to 5.

We also need to solve for Y. Since we got X = 1/2, substitute 1/2 for X in either equation, preferably the original (or first) equation.

y = 3x - 5

y = 3(1/2) - 5

Simplify

y = -7/2

Therefore, x = 1/2, and y= -7/2 OR (1/2, -7/2)